2016
DOI: 10.1097/md.0000000000003582
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Implication of Inflammation-Based Prognostic Score in Pancreatic Cancer

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
85
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(87 citation statements)
references
References 33 publications
2
85
0
Order By: Relevance
“…A number of studies have also found similar results for the prognostic role CAR or GPS in various types of cancers. [7][8][9][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62] This highlighted the general prognostic role of these two inflammation-based scores in malignancies.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have also found similar results for the prognostic role CAR or GPS in various types of cancers. [7][8][9][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62] This highlighted the general prognostic role of these two inflammation-based scores in malignancies.…”
Section: Discussionmentioning
confidence: 99%
“…GPS was derived from the acute-phase proteins C-reactive protein and albumin, which were more sensitive and reliable markers that reflect the systemic inflammatory response in cancer patients. Until now, GPS has been shown to be a favorable predictor of survival in patients with various cancers [30,31,32,33]. Recently, more researchers are focusing on investigating the modified GPS, named mGPS, which also is a combination of C-reactive protein and albumin [34].…”
Section: Discussionmentioning
confidence: 99%
“…There are many reports concerning the relation between each inflammation-based marker and the prognosis of PDAC, but there are few reports comparing the utility of several inflammation-based markers. Yamada et al (21) conducted a retrospective study to clarify which score could best reflect survival in resected pancreatic cancer patients and found that GPS was superior to the other markers. Additionally, a systematic review summarized past reports Table IV.…”
Section: Univariate Multivariate ------------------------------------mentioning
confidence: 99%